THE INFLUENCE OF PERCEIVED ENJOYMENT ON IMPULSIVE BUYING BEHAVIOUR IN THE APPAREL INDUSTRY AMONG MILLENNIALS IN KLANG VALLEY, MALAYSIA - Baskaran , Munish; Dada , Morakinyo (Electronic Journal of Business and Management, 2022)
Millennials today have significant spending power and digital literacy, yet they often exhibit a proclivity for impulsive online purchases. This behavior, characterized by the absence of logical thinking, is driven by the vast amount of time spent online. However, it can lead to negative outcomes such as overspending and financial debt. This study employed a quantitative analysis to investigate factors leading to impulsive buying behavior among millennials in Klang Valley, Malaysia. Based on a sample size of 140 respondents, the findings revealed that perceived enjoyment and personal behavior of millennials are significant attributes that result in impulsive online purchases within the apparel industry.